UJARAN KEBENCIAN (KHITĀB AL-KARĀHIYAH) DALAM RUANG KONTESTASI SOSIAL POLITIK ARAB KONTEMPORER - Yoyo, Yoyo (Adabiyyāt: Jurnal Bahasa dan Sastra, 2019)
The collapse of most authoritarian rulers in the Arab world in particular and the Middle East in general, was automatically followed by a wider change in the direction of political policy and freedom of expression (hurriyyah al-ta'bīr), channeled through various social media. The freedom of expression does not always have positive implications but is accompanied by the growth of expressions of hatred. Hate speech or khitāb al-karāhiyah contri-butes to the social and political contestation of the Arab Arab World. The research questions in this study are as follow (1) what factors are behind the emergence of hate speech in the Arab world?(2) what is the form and type of hate speech that occurs in the Arab socio-political context? and (3) what is the meaning behind the hate speech? The primary research data were newspapers, journals, related books, and supporting data obtained online. These data were analyzed qualitatively based on the sequence of research formulation. The data analyzed with a socio-pragmatic approach combined with a discourse analysis approach that views language as a social symbol. The results of the study show that (1) hate speech in the context of the Arab World emerged from diverse contexts such as the clash among football supporters, Sunni vs. Shia, and the tensions among rebel groups and the rulers, and the peak of the hate speech occurred during the Arab Spring; (2) though hate speech may be expressed using neutral terms, it essentially refers to a particular discourse; (3) forms of hate speech are contained in the selection of words that are rude, dirty, and hateful; 4) forms of hate speech are expressed in the form of revolutionary slogans. These three forms of hate speech have a referential meaning towards the social facts that occur, namely in the form of the guiding of certain political discourses such as criticism of the Mubarak regime, hatred of certain social groups such as the IM, hatred of political figures, and incitement to commit criminal acts.